Motivation deficits and use of alcohol and illicit drugs among individuals with schizophrenia. (July 2017) - Bahorik, Amber L.; Greeno, Catherine G.; Cochran, Gerald; Cornelius, Jack R.; Eack, Shaun M.
Abstract: This study examined the impact of substance use on intrinsic motivation and evaluated the association between intrinsic motivation and substance use recovery among individuals with schizophrenia. Alcohol and illicit drug use and intrinsic motivation were evaluated at baseline and 6-months for 1434 individuals with schizophrenia from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) using self-rated substance use assessments and a derived motivation measure from the Heinrichs-Carpenter Quality of Life Scale. Results revealed patients had moderate motivation deficits overall and a considerable number were using alcohol or illicit drugs at baseline ( n =576; 40.2%). Regression models at baseline showed patients with low levels of motivation had higher odds of substance use and those who were using substances had greater motivation deficits. At 6-months, substance using patients continued to demonstrate greater motivation deficits; however, those with high levels of motivation exhibited a greater reduction in their use of substances. Findings remained significant after adjusting for clinical confounds and were consistent across any substance, alcohol, and cannabis use. Our results emphasize concerns about substance use compounding motivation deficits in schizophrenia, and suggest that disentangling the motivation-substance use relationship in schizophrenia may facilitate efforts aimed at ameliorating these challenges and improving outcomes. Highlights: Overall, patients with schizophrenia had moderate intrinsic motivation deficits. Low motivation ins chizophrenia patients was associated with higher odds of substance use. Continued substance use was associated with greater motivation deficits over the study. Higher motivation levels was associated with faster reductions in substance use over the study.